The Impact of Governance on Financial Institution and Financial Market Development: Empirical Evidence From Emerging Markets - Feyisa, Habtamu Legese; Mamo , Wondmagegn Biru; Yitayaw, Mekonnen Kumlachew (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
The overall objective of the study is to investigate the impact of governance on financial development in Sub-Saharan African countries. To achieve the stated objective, the study employed balanced data of 43 Sub-Saharan African countries during the year 2002 to 2018. To analyze the data, the study used both the fixed and random effect estimation approaches and explored the relationship between the three dimensions of governance and three pillars of financial development in Sub-Saharan African countries. The study also applied the Principal Component Analysis (PCA) to create indexes for the political, economic, and institutional dimensions of governance taking the six world governance indicators. The overall findings of the study indicate that the political, economic, and overall governance composite index has a positive and significant impact on the overall financial developments of sub-Saharan African countries. The development of financial institutions in the region is influenced significantly and positively by political, institutional, and overall governance. In addition, the economic dimension of governance has had a significant and positive impact on the development of the financial markets in sub-Saharan Africa. Furthermore, trade openness, real interest rate, inflation, real GDP, and access to electricity are all major macroeconomic predictors of financial development, according to the study. As a result, all aspects of governance quality in the Sub-Saharan African countries must be improved. This can be achieved by policies aimed at strengthening voice and accountability, political stability, government effectiveness, regulatory quality, rule of law, corruption control, and overall macroeconomic reform.